Making a World after Empire : The Bandung Moment and Its Political Afterlives - Lee, Christopher J. (Book collections on Project MUSE., 2019)
In April 1955, twenty-nine countries from Africa, Asia, and the Middle East came together for a diplomatic conference in Bandung, Indonesia, intending to define the direction of the postcolonial world.